Ethics and Morality: Comparing Ethical Leadership with Servant, Authentic and Transformational Leadership Styles - Muhammad Yasir; Noor Azmi Mohamad (International Review of Management and Marketing, 2016)
This study intends to review a scholarly research on several leadership approaches and its development. This study also provides a comparison of ethical leadership with servant, authentic and transformational leadership styles in the perspective of ethics and morality. This study suggests to the top-management of organizations to adopt and exhibit ethical leadership behavior, because the concept of ethical leadership specifically focuses upon moral and ethical aspects of leadership behavior. Whereas, servant, authentic and transformational leaders do not specifically focus on ethical behavior, thus these leaders may or may not always be ethical depending upon their moral values. Lastly, suggestions for advancing research on ethical leadership in the future are provided.